Remember the Seventies : A Pictorial History of a Stirring Decade - Parragon (Bath, England Parragon, 2011)
A flashback on the world's major events in politics, sports, fashion, science and the arts Packed with over 400 brilliant photos from the Getty Archive Vintage cover design DVD with 30 minutes of stunning archive film footage from the Getty Archives.
Include Color Illustration and Index
Keywords: Nineteen seventies -- Popular culture -- Social change